Penggunaan Analytical Hierarchy Process dan Analytic Network Process dalam Menentukan Supplier Bahan Baku - Indri Parwati, Cyrilla; Hindarto Wibowo, Agus; Safiq Sakh Putra, Mohamad (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2024)
Industry player, navigates the competitive convection business by strategically selecting raw material suppliers, with a focus on fabric. Employing the Analytical Hierarchy Process (AHP), a decision analysis method by Thomas L. Saaty, the company evaluates criteria such as price, quality, delivery, service, and location. In parallel, the Analytic Network Process (ANP), a more intricate method by Saaty, is utilized to account for reciprocal relationships within decision-making hierarchies. The company evaluates three alternative fabric suppliers: Kumala Textile, PT Kaha Tex, and PT Ada Tex. AHP calculations assign priority values – Kumala Textile at 0.381187, PT Kaha Tex at 0.470966, and PT Ada Tex at 0.073924. Concurrently, ANP prioritizes alternatives differently: Kumala Textile at 0.315383, PT Kaha Tex at 0.565728, and PT Ada Tex at 0.118889. Considering the results, PT Kaha Tex emerges as the most optimal raw material supplier with a dual-method endorsement. Kumala Textile secures the second recommendation, while PT Ada Tex takes the third spot. Selection criteria for fabric raw material suppliers encompass price, quality, delivery, service, and location. Grounded in prioritization values and criterion relationships, the comprehensive recommendation is in favor of PT Kaha Tex as the most optimal fabric raw material supplier.